Efektivitas Penggunaan Periodic Table Of Ladder Terhadap Hasil Belajar Siswa Pada Materi Tabel Periodik Unsur Kelas X SMKN 1 BP BR - Diana Novitasari; Varona Maharani; Salysa Eka Nabila (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research is motivated by the lack of availability of learning media usage and conventional learning. Therefore, an effectiveness test of the periodic table of the ladder media was conducted to improve the learning outcomes of students at SMKN 1 BP BR on the topic of periodic table of elements. This research is a pre-experimental study aimed at assessing the effectiveness of media usage using data analysis techniques through pretest-posttest assessments. The population in this study is the students of class X TBSM SMKN 1 BP BR. The research instrument is a learning outcomes test consisting of 25 multiple-choice questions that have been pilot tested. The data analysis techniques used are the t-test to determine differences in learning outcomes and the N-Gain test to determine the improvement in students' understanding. The results of the study show that there are differences and improvements in students' learning outcomes. This is evidenced by the average posttest score of 86.67. The improvement in learning outcomes is also supported by hypothesis testing conducted with the t-test, obtaining a t-value (3.45) > t-table (1.21). Another supporting evidence is the average N-Gain test score of 0.75 with a high category. Thus, it can be concluded that the use of the periodic table of the ladder media is effective in improving students' learning outcomes with a high category. This media is suitable for chemistry learning that is symbolic, as it will be more engaging and challenging through direct student involvement in the learning process.